2007
DOI: 10.1080/01635580701525877
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Methionine-Free Diet Duration for Nitrourea Treatment: A Phase I Clinical Trial

Abstract: In animal models, methionine (MET) restriction in association with chloroethylnitrosoureas led to a substantial improvement. On this basis, we initiated a Phase I clinical trial of dietary MET restriction in association with chloroethylnitrosourea (cystemustine) treatment for patients with recurrent glioma or metastatic melanoma. Our purpose was 1) to determine the optimal MET-free diet duration for a maximum depletion of plasma MET and 2) to evaluate the feasibility of this association. A total of 10 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 25 publications
1
42
0
Order By: Relevance
“…This reduction threshold for plasma MET was consistent with previous reports in healthy men [22] on an oral MET-free diet (49% at 3 h, 60% at 2 days) and in patients with metastatic solid cancer [23]with enteral MET restriction (42% at 4 days). In our previous phase I clinical trial testing the association of a MET-free diet with nitrosourea chemotherapy in metastatic melanoma and recurrent gliomas, the MET-free diet induced a maximal decrease of 55% in the plasma MET concentration 4 h after beginning diet administration without an effect on the extent of the MET-free diet period [24]. Indeed, we confirmed the lack of any cumulative effect of diet on plasma MET concentrations which could be linked to the daily increase in MET level during overnight fasting.…”
Section: Discussionmentioning
confidence: 99%
“…This reduction threshold for plasma MET was consistent with previous reports in healthy men [22] on an oral MET-free diet (49% at 3 h, 60% at 2 days) and in patients with metastatic solid cancer [23]with enteral MET restriction (42% at 4 days). In our previous phase I clinical trial testing the association of a MET-free diet with nitrosourea chemotherapy in metastatic melanoma and recurrent gliomas, the MET-free diet induced a maximal decrease of 55% in the plasma MET concentration 4 h after beginning diet administration without an effect on the extent of the MET-free diet period [24]. Indeed, we confirmed the lack of any cumulative effect of diet on plasma MET concentrations which could be linked to the daily increase in MET level during overnight fasting.…”
Section: Discussionmentioning
confidence: 99%
“…In neither group did we observe a significant change in body weight while on the diet. In comparison, an approximately 40% decrease of plasma Met was previously reported on the first day of a Met-free regimen, which was a more stringent, formulabased Met-free diet [12].…”
Section: Mr Effects On Clinical Patients With Crohn's Diseasementioning
confidence: 94%
“…Data from a phase I clinical trial conducted on 8 patients with metastatic solid tumors by Epner and colleagues indicated for the first time that diet with a reduced Met content is safe and feasible to treat patients with cancer, despite a conclusive lack of sufficient anti-tumor activity [10,11]. A Met-free diet was used in con-junction with other anti-cancer agents in another two Phase I clinical trials [12,13]. Both regimens were found to be relatively feasible and well tolerated, one of which resulted in partial response to the therapy and disease stabilization among 4 evaluated patients [13].…”
Section: Methionine Restriction In Aging and Can-cer Studiesmentioning
confidence: 99%
“…132 In a Phase I trial with 10 patients with recurrent glioma and metastatic melanoma, the optimal duration of a MET-free diet for maximum depletion of plasma level was determined to be 1 day, leading to a depletion level of 41%. 133 The patients tolerated four cycles of 2 weeks of a MET-free diet in combination with cystemustine treatment. 133 Based on these results, a clinical Phase II trial was initiated with 20 patients with metastatic melanoma and two recurrent glioma receiving four cycles of cystemustine every second week in combination with a MET-free diet.…”
mentioning
confidence: 99%
“…133 The patients tolerated four cycles of 2 weeks of a MET-free diet in combination with cystemustine treatment. 133 Based on these results, a clinical Phase II trial was initiated with 20 patients with metastatic melanoma and two recurrent glioma receiving four cycles of cystemustine every second week in combination with a MET-free diet. 134 The MET plasma level decreased to 53.1% 6 21.8%.…”
mentioning
confidence: 99%